Acute Histological Chorioamnionitis and Birth Weight in Pregnancies With Preterm Prelabor Rupture of Membranes: A Retrospective Cohort Study - Matulova, Jana; Kacerovsky, Marian; Hornychova, Helena; Stranik, Jaroslav; Mls, Jan; Spacek, Richard; Burckova, Hana; Jacobsson, Bo; Musilova, Ivana (Frontiers in Pharmacology, 2022)
Aim: To assess the association between the birth weight of newborns from pregnancies with preterm prelabor rupture of membranes (PPROM) and the presence of acute histological chorioamnionitis (HCA) with respect to the: i) fetal and maternal inflammatory responses and ii) acute inflammation of the amnion. Material and Methods: This retrospective cohort study included 818 women with PPROM. A histopathological examination of the placenta was performed. Fetal inflammatory response was defined as the presence of any neutrophils in umbilical cord (histological grades 1-4) and/or chorionic vasculitis (histological grade 4 for the chorionic plate). Maternal inflammatory response was defined as the presence of histological grade 3-4 for the chorion-decidua and/or grade 3 for the chorionic plate and/or grade 1-4 for the amnion. Acute inflammation of the amnion was defined as the presence of any neutrophils in the amnion (histological grade 1-4 for the amnion). Birth weights of newborns were expressed as percentiles derived from INTERGROWTH-21st standards for the i) estimated fetal weight and ii) newborn birth weight. Results: No difference in percentiles of birth weights of newborns was found among the women with the women with HCA with fetal inflammatory response, with HCA with maternal inflammatory response and those without HCA. Women with HCA with acute inflammation of the amnion had lower percentiles of birth weights of newborns, derived from the estimated fetal weight standards, than women with HCA without acute inflammation of the amnion and those with the absence of HCA in the crude (with acute inflammation: median 46, without acute inflammation: median 52, the absence of HCA: median 55; p = 0.004) and adjusted (p = 0.02) analyses. The same subset of pregnancies exhibited the highest rate of newborns with a birth weight of ≤ 25 percentile. When percentiles were derived from the newborn weight standards, no differences in birth weights were observed among the subgroups. Conclusions: Acute inflammation of the amnion was associated with a lower birth weight in PPROM pregnancies, expressed as percentiles derived from the estimated fetal weight standards.